Symbolic action and organizational resources acquisition and exploitation = Działania symboliczne a nabywanie i eksploatacja zasobów organizacji - Mazur, Karolina (Zielona Góra: Faculty of Economics and Management Press)
The article aims to analyze the current literature (conceptual and research articles) in the field of relations between the symbolic activities of the organization and the ability to acquire resources and their efficient exploitation, and an attempt to build a conceptual model on this basis. This goal was achieved by applying a systematic literature review.
Keywords: działania symboliczne; kapitał symboliczny; zasoby organizacji; zasoby symboliczne; symbolic activities; symbolic capital; organizations resources; symbolic resources